2015
DOI: 10.1158/1055-9965.epi-14-1389
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Recent Skin Examination in a Population-Based Twin Cohort

Abstract: Background The incidence of melanoma is increasing worldwide. Guidelines for clinical skin exam for improving early diagnosis of melanoma remain inconsistent, and current data on factors associated with regular skin screening on a population basis are limited. Methods We used self-reported data from 50,044 members of the California Twin Program, a population-based cohort of twins born in California between 1908 and 1982, to identify prevalence and determinants of recent clinical screening for skin cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…This figure is higher than the overall rate of 21.3% in the U.S. population in 2015 [ 10 ]. Higher rates of screening were found among individuals with one or more skin cancer risk factors, which is consistent with research conducted with non-veteran populations [ 10 , 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…This figure is higher than the overall rate of 21.3% in the U.S. population in 2015 [ 10 ]. Higher rates of screening were found among individuals with one or more skin cancer risk factors, which is consistent with research conducted with non-veteran populations [ 10 , 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our data do not contain a direct measure of skin cancer screening. To account for potential surveillance bias among users of MHT, we examined the following correlates of skin cancer screening: education, age, marital status, constitutional characteristics (hair color and skin complexion), 27 29 and dental x-rays because dental visits are associated with access and use of preventative care. 19 – 22 Missing values were coded as separate categories and included as indicator variables in the models.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the significantly lower frequency of physician skin checks reported by American Indian individuals ( P < .001) in this study may be associated with the higher melanoma mortality rates among the American Indian population. Although there is a paucity of data for comparison, a similar study found non-Hispanic white people to be more likely than nonwhite individuals to have physician skin checks . Data from 1999 to 2006 showed high percentages of advanced, thicker melanomas among nonwhite compared with white persons .…”
Section: Discussionmentioning
confidence: 98%
“…Although there is a paucity of data for comparison, a similar study found non-Hispanic white people to be more likely than nonwhite individuals to have physician skin checks. 4 Data from 1999 to 2006 showed high percentages of advanced, thicker melanomas among nonwhite compared with white persons. 4,5 The higher percentage of Related article page 1342 A 2-sample t test indicated a statistically significant difference in mean sun-behavior scores between American Indian and non-Hispanic white participants (P < .001) with overall sun-behavior scores higher among non-Hispanic white participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation